Teaching reflection of using technology in two Indonesian EFL classrooms: an autoethnography - Yustinus Calvin Gai Mali (Journal on English as a Foreign Language, 2022)
Integrating technology in EFL writing classrooms is a trial-and-error process that requires teachers to reflect, constructively analyze their practices, and have the flexibility to make positive changes to their teaching with technology. Using various data sources of my students’ blog, written assignments, and online interactions, this qualitative autoethnography study reflects upon my experiences as a lecturer in integrating technology in two EFL writing classes at the English Language Education Program of a private university in Central Java, Indonesia. Based on my written reflections narrated in the findings’ section, I discussed five main themes (i.e., struggle, unsuitable choice of technology, not a magic stick, traditional ingredients, and learning from one another) as the answer to the research question of this study. Overall, these five themes detailed my teaching practices in the classrooms, personal feelings of using technology, teaching and learning challenges of using technology in the writing classes, and possible solutions to deal with those challenges. This study might illustrate how reflecting on teaching experiences allows teachers to be aware of what they did in a class, find areas that need improvement, and plan for teaching-related changes in their future classrooms. Meanings of integrating technology in the classrooms and recommendations for further research are presented.